Answers

2016-02-14T21:59:04+05:30
Let the terms be a-d, a, a+d
by question (a-d)+ a + (a+d)=24 
=> 3a=24
=>a=6.......................................... (1)

now by another condition a(a+d)(a-d)=440
=> a(a²- d²) = 440
=> 6(36 - d²)= 440
=> 36-d²=440/6
=> -d²=440/6 - 36
=> -d² = 37.333
=> d=-6.110
thus a= 6 and d = -6 aritmatically....

0
thus ap are 6-6, 6, 6+6 
sorry 12, 6, 0
if possible plz mark it brainiest... 
2016-02-14T22:18:42+05:30
Let the no are a-d,a, a+d
a-d+a+a+d=24
3a=24
a=8
(a-d)(a)(a+d)=440
(8-d)(8)(8+d)=440
8^2-d^2=440/8
64-d^2=55
-d^2=55-64
-d^2=-9
d=3
1 5 1